Hubungan Jarak Jamban Terhadap Kandungan Bakteri Fecal Coliform Pada Air Sumur Gali Desa Kuranji Di Nagari Lubuk Jantan - Helma Novita Rolisa; Leila Muhelni (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Domestic waste that is disposed of carelessly is one of the causes of soil pollution. This research was conducted in the village of Kuranji Nagari Lubuk Jantan, the measurement result are filled in based on meansuring the distance from the latrine to the dug well using a meter. Fecal Coliform variable, the MPN (Most Probable Number) test was used on dug well water with reference to SNI 06-4158-1996 at the Andalas University Water Laboratory. Of the 31 dug well facilities, there are 31 dug well facilities (100%) that have well water with Fecal Coliform that does not meet the requirements in accordance with the 2017. Research result that: 1. Based on the proportion of fecal coliform in Kuranji village, laboratory test result on 31 dug well samples do not meet the requirements for direct consumption in RI Minister of Health Regulation No. 416/Menkes/per/IX/1990 with a percentage of 100%. 2. The potential spread of fecal coliform contamination is due to inadequate contruction. 3. Of the 31 samples of dug wells and latrines that were observed, 23 dug wells had an unsatisfactory contamination distance of 11 meters with a contamination rate of 29 with a percentage of (93.55), 2 dug wells had a satisfactory distance to the latrine of 11 meters with a percentage of 6.50%.